THE RELATIONSHIP BETWEEN JOB SECURITY AND EMPLOYEE PERFORMANCE IN KOLE DISTRICT LOCAL GOVERNMENT: A DESCRIPTIVE, CORRELATIONAL STUDY. - Ongom, Fred Ojok; Kyokunda, Evelyne Hope (Student's Journal of Health Research Africa, 2023)
Background This study aims to determine the relationship between job security and employee performance in Kole District Local Government. Methodology The research was a descriptive, correlational research design that was cross-sectional. The target population of this study was 124 employees of Kole District local government. The researcher adopted the Morgan & Kreijcie sampling table to determine the sample size and 92 staff were selected as respondents of the study. Simple random sampling techniques and purposive sampling were used to select respondents for the study. This research used both primary and secondary sources of data. Primary data was obtained and given to the selected staff of the Kole district to fill and return after one week. Results According to the findings, wages paid to employees at Kole District Local Government were not sufficient to satisfy their needs and support their growth. Further, findings showed that there was no formalized career path for employees at Kole district local government. Findings also revealed that there was limited access to leadership and management roles hence limiting growth of employees and low employee performance. Kole District Local Government had numerous job openings which make it easy for employees to move up the ladder and explore their potential. Also, findings showed that Kole District Local Government offers professional development opportunities for employees and enables career progress through employee training. Findings also showed that respondents agreed that in the Kole district, employees are not recognized for providing extra effort hence employees are demotivated to offer quality services. Conclusion There was a positive significant relationship (r = 0.325, sig 0.004) between job security and employee performance of employees at Kole District. Recommendation Kole District local government should ensure systematic restructuring and phased transfers for different job roles to enhance the skills of employees and improve productivity.